(untitled) (Ustozlar uchun, 2025)
This article examines the scientific foundations and historical development of physiology, its essential role in modern medicine, and its contribution to understanding functional regulation and systemic integration within the human organism. Through analysis of classical physiological theories and contemporary biomedical research, the study explores neurohumoral regulation, homeostatic mechanisms, and the integrative principles that maintain the organism as a unified biological system. Furthermore, the article investigates the nature of bioelectrical phenomena in excitable tissues, including the mechanisms of resting membrane potential and action potential generation in nerve and muscle cells. Drawing upon contributions from modern physiology, neurobiology, and clinical diagnostics, the study emphasizes physiology’s central role in medical science and its importance for understanding disease, developing therapeutic strategies, and advancing biomedical technologies. The findings demonstrate that physiology forms the conceptual core of clinical reasoning and remains indispensable for interpreting normal and pathological states of the human body.¹